Describing the characteristics, treatment pathways, outcomes, and costs of people with persistent noncancer pain managed by community pain clinics and generating an indicative estimate of cost-effectiveness: feasibility study protocol - AlAujan, Shiekha; AlMazrou, Saja; Knaggs, Roger D.; Elliott, Rachel A. (Dove Medical Press, 2016)
BACKGROUND